Improvement of sliding mode power control applied to wind system based on doubly-fed induction generator - Btissam Majout; Douae Abrahmi; Yasmine Ihedrane; Chakib El Bakkali; Karim Mohammed; Badre Bossoufi (Institute of Advanced Engineering and Science, 2021)
In this work, we are interested in improving the performance of a doubly-fed induction generator (DFIG)-based wind system, by applying a sliding mode control strategy. The objective is the regulation of the active and reactive power, also the voltage and the frequency of the signal injected into the distribution network. The model proposed for the control is based on the sliding mode technique with performance estimators. The proposed model was validated by a simulation on MATLAB/Simulink.